Fishers' ecological knowledge of smalleye hammerhead, Sphyrna tudes , in a tropical estuary - Giglio,Vinicius J. (2016)
ABSTRACT Coastal hammerheads have suffered from overexploitation and environmental degradation. We interviewed 79 artisanal fishers to verify fishery aspects, temporal changes in catches and biological aspects of the smalleye hammerhead, Sphyrna tudes , in a marine protected area on Abrolhos Bank, Brazil. Data were compared between three generations of fishers: young, middle-aged and old. Fishers' age varied between 17 and 88 years. We verified significant reductions in the weight of individuals caught by younger fishers. The main types of fishing gear used to catch S. tudes were gill nets and longlines. Overfishing through gill nets and trawl fisheries were mentioned as the cause of S. tudes population collapse in the region. The shark's diet as reported by fishers consisted of fish, crab and shrimp; austral summer was the reproductive season. A strong similarity was verified between fishers' knowledge and biological data. We suggest as plausible strategies to conserve the local population of S. tudes the reduction of net fisheries impact through zoning and establishment of no take areas. These steps can help to initiate the recovery of this depleted species.